Comparative analysis of alternative polyadenylation in S. cerevisiae and S. pombe - Liu, Xiaochuan; Hoque, Mainul; Larochelle, Marc; Lemay, Jean-François; Yurko, Nathan; Manley, James L.; Bachand, François; Tian, Bin

(untitled) (Genome Research, 2017)
Alternative polyadenylation (APA) is a widespread mechanism that generates mRNA isoforms with distinct properties. Here we have systematically mapped and compared cleavage and polyadenylation sites (PASs) in two yeast species, S. cerevisiae and S. pombe. Although >80% of the mRNA genes in each species were found to display APA, S. pombe showed greater 3′ UTR size differences among APA isoforms than did S. cerevisiae. PASs in different locations of gene are surrounded with distinct sequences in both species and are often associated with motifs involved in the Nrd1-Nab3-Sen1 termination pathway. In S. pombe, strong motifs surrounding distal PASs lead to higher abundances of long 3′ UTR isoforms than short ones, a feature that is opposite in S. cerevisiae. Differences in PAS placement between convergent genes lead to starkly different antisense transcript landscapes between budding and fission yeasts. In both species, short 3′ UTR isoforms are more likely to be expressed when cells are growing in nutrient-rich media, although different gene groups are affected in each species. Significantly, 3′ UTR shortening in S. pombe coordinates with up-regulation of expression for genes involved in translation during cell proliferation. Using S. pombe strains deficient for Pcf11 or Pab2, we show that reduced expression of 3′-end processing factors lengthens 3′ UTR, with Pcf11 having a more potent effect than Pab2. Taken together, our data indicate that APA mechanisms in S. pombe and S. cerevisiae are largely different: S. pombe has many of the APA features of higher species, and Pab2 in S. pombe has a different role in APA regulation than its mammalian homolog, PABPN1.